2014
DOI: 10.1108/ijrd-08-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing attrition from a researcher training program

Abstract: Purpose – This study explored attrition from a novice health researcher training program. The aim of this paper was to identify factors contributing to attrition from the RRCBP that if understood could decrease attrition from this standalone researcher training program. Design/methodology/approach – Using a capacity building framework, this case-control study compared demographic characteristics and features of 30 withdrawn research trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Existing research training options available to staff are not well advertised and there was limited awareness of some public sector training options [5,12,13]. Those with an interest in learning about research are doing so via external institutions as research higher degrees which may increase individual skill but limits the organisational benefit of this activity as there is limited opportunity to align these projects with organisational goals, which should provide a supportive structure in which individuals can receive support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing research training options available to staff are not well advertised and there was limited awareness of some public sector training options [5,12,13]. Those with an interest in learning about research are doing so via external institutions as research higher degrees which may increase individual skill but limits the organisational benefit of this activity as there is limited opportunity to align these projects with organisational goals, which should provide a supportive structure in which individuals can receive support.…”
Section: Discussionmentioning
confidence: 99%
“…While research is seen as an individual preference or activity it remains external to the organisation's activities and priorities. This individual motivation is seen as important for research completion [21,22], although this is not evidenced in rural areas [5]. Individuals undertaking research education via universities are given little encouragement to subsequently use these skills within the organisation, evidence of a cultural structure which inhibits individual agency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 A subsequent study found a reason for non-completion for some program candidates was a lack of organisational support. 18 While both studies demonstrated aspects associated with completion of research, evidence of research experience building as a result of investing in workplace-based research training via the RRCBP has not been presented.…”
Section: Introductionmentioning
confidence: 99%